2007
DOI: 10.1186/1471-2121-8-51
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and AMP kinase activator stimulate proliferation, differentiation, and mineralization of osteoblastic MC3T3-E1 cells

Abstract: Background: Adiponectin is a key mediator of the metabolic syndrome that is caused by visceral fat accumulation. Adiponectin and its receptors are known to be expressed in osteoblasts, but their actions with regard to bone metabolism are still unclear. In this study, we investigated the effects of adiponectin on the proliferation, differentiation, and mineralization of osteoblastic MC3T3-E1 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
127
1
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(145 citation statements)
references
References 52 publications
7
127
1
10
Order By: Relevance
“…147 Paradoxically, adiponectin which is secreted nearly exclusively by adipocytes has been found to prevent adipogenic differentiation in bone marrow cultures and increase trabecular bone mass by promoting osteoblastogenesis and repressing osteoclast formation. [148][149][150][151] Unlike adiponectin, the expression of leptin increases concurrently with adiposity and appears to be unaffected by diabetes. [152][153][154] Leptin appears to have contradictory effects on bone, activating the sympathetic nervous system to accelerate bone loss, as well as stimulating the osteogenic differentiation of marrow MPCs, with the net outcome dependent on its concentration.…”
Section: Diabetic Medicationsmentioning
confidence: 99%
“…147 Paradoxically, adiponectin which is secreted nearly exclusively by adipocytes has been found to prevent adipogenic differentiation in bone marrow cultures and increase trabecular bone mass by promoting osteoblastogenesis and repressing osteoclast formation. [148][149][150][151] Unlike adiponectin, the expression of leptin increases concurrently with adiposity and appears to be unaffected by diabetes. [152][153][154] Leptin appears to have contradictory effects on bone, activating the sympathetic nervous system to accelerate bone loss, as well as stimulating the osteogenic differentiation of marrow MPCs, with the net outcome dependent on its concentration.…”
Section: Diabetic Medicationsmentioning
confidence: 99%
“…The cells were stained with 2% AgNO 3 and fixed with 2.5% NaS 2 O 3 by von Kossa method to detect phosphate deposits in bone nodules [6][7][8]. At the same time, the order plates were fixed with ice-cold 70% ethanol and stained with Alizarin red to detect calcification.…”
Section: Assay Of Mineralizationmentioning
confidence: 99%
“…SYBR green chemistry was used to perform quantitative determinations of the mRNAs for BMP-2, collagen-I, osteocalcin, and a house keeping gene, 36B4, according to an optimized protocol [6][7][8][9]. Total RNA was taken from cultured C3H10T1/2 and ST2 cells using Trizol reagent (Invitrogen, San Diego, CA) according to the manufacturer's recommended protocol.…”
Section: Real-time Pcr Quantification Of Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel findings, described in detail in this review, have shown that AMPK plays a role in bone physiology. There are in vitro studies demonstrating that AMPK modulators regulate bone cell differentiation and function (Kanazawa et al 2007, Molinuevo et al 2010, Quinn et al 2010, Shah et al 2010, Jang et al 2011, Mai et al 2011 and two publications showing that deletions of AMPKa and b subunits in mice lead to bone loss in vivo (Quinn et al 2010, Shah et al 2010. Furthermore, AMPK activity can be regulated in bone cells by hormones, such as ghrelin and norepinephrine, that regulate food intake and energy expenditure through AMPK activation in the brain and peripheral tissues.…”
Section: Introductionmentioning
confidence: 99%